2020
DOI: 10.4081/oncol.2020.448
|View full text |Cite
|
Sign up to set email alerts
|

Role of membrane-embedded drug efflux ABC transporters in the cancer chemotherapy

Abstract: One of the major problems being faced by researchers and clinicians in leukemic treatment is the development of multidrug resistance (MDR) which restrict the action of several tyrosine kinase inhibitors (TKIs). MDR is a major obstacle to the success of cancer chemotherapy. The mechanism of MDR involves active drug efflux transport of ABC superfamily of proteins such as Pglycoprotein (P-gp/ABCB1), multidrug resistance-associated protein 2 (MRP2/ABCC2), and breast cancer resistance protein (BCRP/ABCG2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 127 publications
0
32
0
Order By: Relevance
“…Increasing evidence illustrates that miRNAs are implicated in the expansion and development of MDR in tumour cells by modulating the expression of different protein translation targets (Lee et al., 2020; Zhu et al., 2020). Hence, the comprehensive understanding of the mechanism of miRNAs regulation may contribute to the improvement of MDR‐reversing agents (Gupta et al., 2020). Lu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence illustrates that miRNAs are implicated in the expansion and development of MDR in tumour cells by modulating the expression of different protein translation targets (Lee et al., 2020; Zhu et al., 2020). Hence, the comprehensive understanding of the mechanism of miRNAs regulation may contribute to the improvement of MDR‐reversing agents (Gupta et al., 2020). Lu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al, 2020). Hence, the comprehensive understanding of the mechanism of miRNAs regulation may contribute to the improvement of MDR-reversing agents (Gupta et al, 2020). revealed that miR-21 is overexpressed in 15 malignancy kinds, which alleviated the overall survival in 6 types of carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…colchicine, and the vinca alkaloids vinblastine and vincristine inhibit polymerisation of microtubules 17 . Significant attention is now focussed on colchicine binding site inhibitors due to their positive impact on ABC-transporter-mediated drug resistance 18,19 . Combretastatin A-4 (CA-4), (1, Figure 1) has been reported as the most potent antimitotic agent of this family against several tumour cells 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1 , some of the well-known lncRNAs involved in the event of cancer drug resistance have been summarized. The principal mechanisms of drug resistance in cancer cells are: (1) overexpression of drug efflux transporters like ATP-binding cassette (ABC) superfamily pumps [ 97 ]; (2) enhanced repair of chemotherapy induced-genome damages [ 98 ]; (3) alternation signaling pathways controlling drug resistance [ 99 ]; (4) enhanced modulation of drug metabolism; (5) increasing resistance to cell death mechanisms [ 100 ]; and (6) EMT [ 99 ].…”
Section: Role Of Lncrnas In Human Cancersmentioning
confidence: 99%